Motor performance of students with learning difficulties - Okuda, Paola Matiko Martins [UNESP] (2015)
This study aims to characterize and compare the motor performance of students with learning difficulties in relation to students with good academic performance. A total of 20 students were divided into: GI - 10 students with learning difficulties and GII 10 students with good academic performance. Bruininks-Oseretsky Test of Motor Proficiency was applied. The students of GI had inferior performance when compared with GII in the motor areas and motor subtests. The findings can assist in the identification of motor alterations that influence their performance in learning, allowing an educational conduct focused towards minimizing the impact of behavioral and academic manifestations. (C) 2015 The Authors. Published by Elsevier Ltd.